Managing under austerity, delivering under pressure : performance and productivity in public service - Wanna, John; Lee, Hsu-Ann; Yates, Sophie (Research fellow) (ANZSOG (Series), 2015)
Contemporary public managers find themselves under pressure on many fronts. Coming off a sustained period of growth in their funding and some complacency about their performance, they now face an environment of ferocious competitiveness abroad and austerity at home. Public managers across Australia and New Zealand are finding themselves wrestling with expenditure reduction, a smaller public sector overall, sustained demands for productivity improvement, and the imperative to think differently about the optimal distribution of responsibilities between states, markets and citizens. Given ever-shrinking resources, in terms of staffing, budgets and time, how can public managers and public services become more productive, more outcome-driven and more agile? How can we achieve better alignment between ever-growing citizen expectations and the realities of constrained service provision? What can we learn from the best combination of innovation and austerity already being delivered in other countries and sectors, including harnessing the grounded wisdom of frontline service delivery practitioners? This book focuses on practical ways public managers at home and abroad are dealing with these shared dilemmas. It brings together renowned scholars in the fields of public sector productivity, performance management, 'frugal innovation' and budget stringency, with leading international and Australasian practitioners sharing their successes and challenges.